MEDIA PENGENALAN ORGAN TUBUH MANUSIA DALAM BAHASA LATIN UNTUK SISWA SMP BERBASIS ADOBE AFTER EFFECT - Bella Puspita; Herlina Harahap; Sumi Khairani (Universitas Harapan Medan, 2020)
Making media on the introduction of human body organs in Latin based on Adobe After Effect is aimed at junior high school students with the aim and purpose that junior high school students are more interested getting to know the human organs in Latin with this 2D animated video. Making media introduction to human organs in Latin based on Adobe After Effect through three applications, the Adobe After Effect application is used for making animation, Adobe Illustrator to draw all of characters, background settings or other ambience and Adobe Audition as audio editing manager before being combined into Adobe After Effect. The process of making this animation requires a story idea, scene and storyboard. There are several steps to make an animated object to become a 2D animation video, modeling or depiction of background characters and other ambience, audio editing and animation. The result of this animation research is a learning medium for human body organs in Latin for junior high school students which aims to provide information about animation the body organs in the human body along with an explanation.